Switching to tenofovir disoproxil fumarate vs continuing treatment in patients with chronic hepatitis B who maintain long‐term virological response to entecavir therapy: A randomized trial. Issue 7 (12th March 2019) - Iida‐Ueno, Ayako; Enomoto, Masaru; Kozuka, Ritsuzo; Tamori, Akihiro; Kawada, Norifumi
Abstract: No controlled trial in patients with chronic hepatitis B virus (HBV) infection on long‐term entecavir (ETV) treatment, comparing switching to tenofovir disoproxil fumarate (TDF) with continuing the therapy, has been reported. Twenty‐seven nucleos(t)ide‐naïve patients with chronic HBV who underwent ETV therapy for ≥5 years and maintained virological response were included and randomized into two groups: one group continued ETV, and the other switched to TDF, in a 1:2 ratio. The primary endpoint was changed from baseline in serum hepatitis B surface antigen (HBsAg) level at week 48. The baseline characteristics were not different between nineteen patients in the TDF group and eight patients in the ETV group. Mean decreases in HBsAg level at week 48 were 0.023 and 0.042 log10 IU/mL in the TDF and ETV groups, respectively ( P = 0.94). The mean drops in hepatitis B core‐related antigens were also not different between the TDF and ETV groups at week 48 ( P = 0.80). HBV DNA was sustainedly <2.1 log10 copies/mL in all patients throughout the study period. In contrast, the mean aminotransferase levels were significantly higher in the TDF group than in the ETV group at weeks 12, 24, and 36, although being within the reference range. Estimated glomerular filtration rate was lower in the TDF group than in the ETV group at weeks 24 ( P = 0.016) and 48 ( P = 0.003). In conclusion, we could not find the effect on reducing HBsAg level by switching to TDF in chronic hepatitis B patients with maintained virological response to ETV for ≥5 years.